Pelatihan dan Pendampingan Pengelolaan Pembibitan Kelapa Sawit untuk Meningkatkan Kompetensi Petani di Gampong Reuleut Timu, Kabupaten Aceh Utara - Yusuf, Muhamad; Nazirah, Laila; Ismadi, Ismadi; Nilahayati, Nilahayati; Handayani, Rd. Selvy; Humaira, Mira; Ramadhani, Almuna (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2026)
Limited technical knowledge, restricted access to certified oil palm seedlings, and inadequate supporting facilities are the main challenges faced by farmers in Gampong Reuleut Timu, North Aceh Regency. This community service program aimed to strengthen farmers' capacity and self-reliance in oil palm (Elaeis guineensis Jacq.) nursery management. The program was implemented through extension activities, hands-on demonstrations, and continuous mentoring using a capacity-building approach that emphasized active community participation. The program results indicated improvements in participants' knowledge and technical skills in nursery management, enhanced group collaboration, and increased utilization of locally available organic materials to support more sustainable nursery practices. The activities also encouraged community initiatives to establish independent nursery units, develop partnerships with farmer cooperatives, and design collective seedling marketing strategies. These outcomes contributed to strengthening farmers' technical capacity and fostering collaborative community engagement, providing a foundation for the sustainable development of village-based oil palm nursery management using local resources.